Plasma glucose and hemoglobin A1c for the detection of diabetes in Chinese adults. (30th July 2015) - Xu, Yu; Zhao, Wenhua; Wang, Weiqing; Bi, Yufang; Li, Jianhong; Mi, Shengquan; Xu, Min; Lu, Jieli; Wang, Tiange; Li, Mian; Wang, Zhuoqun; Jiang, Yong; et al.
Abstract: Background: The aim of the present study was to evaluate the performance of plasma glucose (PG) and HbA1c for the detection of diabetes in the general population in China. Methods: A cross‐sectional analysis was conducted in a nationally representative sample of 98 658 Chinese adults aged ≥18 years. Fasting plasma glucose and HbA1c levels were measured in all participants after at least a 10‐h overnight fast. An oral glucose tolerance test (OGTT) was conducted among participants without a self‐reported history of diagnosed diabetes. Results: An HbA1c ≥6.5% could identify 4.57% of Chinese adults as having newly detected diabetes, followed by fasting PG (FPG) and 2‐h PG at 4.52% and 3.50%, respectively. Approximately 1.95% of the total population was detected by HbA1c but not by FPG or 2‐h PG. However, FPG plus HbA1c could identify most (85.2%) diabetic individuals identified by any of the three tests (i.e. FPG, 2‐h PG, and HbA1c). Levels of most cardiovascular risk factors, such as body mass index, waist circumference, and cholesterol, were higher in diabetes detected by HbA1c alone than in diabetes identified by the OGTT. Conclusions: Although HbA1c ≥6.5% has been recommended by the American Diabetes Association as one of the diagnostic tests for diabetes, caution should be used to avoid potential overdiagnosis when interpreting diabetes identified by elevated HbA1c alone.